Eco-digital storytelling: Engaging historically excluded populations in environmental action through mentoring, geospatial technology, and digital media storytelling - Cisneros, Laura; Campbell, Todd; Freidenfelds, Nicole; Lindemann, Anna; Elliot-Famularo, Heather; Chadwick, Cary; Dickson, David; Park, Byung-Yeol (Frontiers in Education, 2023)
As the environment, science, technology, engineering, arts, and mathematics fields (a collection of fields we call E-STEAM) grow and remain economically important, historically excluded groups remain underrepresented in science and technology professions, with representation well below that of the general population in the United States, particularly in environmental and digital media fields. As such, building pathways for historically excluded students to be prepared and qualified to enter economically viable E-STEAM professions is both ethically important and critical to increasing innovation within these fields and ensuring a multiplicity of representation as these fields continue to be shaped and reshaped in transformational ways to attend to the plural interests of diverse communities. Consequently, this conceptual paper describes an eco-digital storytelling (EDS) approach to engaging historically excluded populations in STEM that offers structured learning opportunities connected to learner interests and community needs with the aim of increasing E-STEAM identity and career interest of teens from historically excluded groups in E-STEAM fields. E-STEAM identity is a meaning one can attach to oneself or that can be ascribed externally by others as individuals interact and engage in E-STEAM fields to foreground a focus on the environment. The EDS approach leverages community-based action, technology and digital media, and arts and storytelling as an entry point for engaging learners. More specifically, this approach is grounded in state-of-the-art geospatial and digital media technology and seeks to support teens to contribute to local environmental solutions as they engage in science communication. EDS is designed to increase teens’ content knowledge within multiple E-STEAM fields and provide numerous technology-rich experiences in both application of geospatial technologies (i.e., GPS, drones, interactive maps) and digital media creation (i.e., video, animation, ArcGIS StoryMaps) as a way to shape teens’ cultural learning pathways or the learning that occurs over the lifespan across experiences that are shaped by cultural and community knowledge and values. Examples of rich digital media presentations developed to communicate the EDS approach and local environmental opportunities, challenges, and projects are provided that exemplify the powerful ways both participation in and communication of environmental action can contribute to more promising and sustainable futures.